Análise em bacias hidrográficas: contribuição metodológica para o diagnóstico ambiental - Carvalho, Ana Gabriela Bueno Melo de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The small watersheds directly influence the quality of life of the cities, and the methodologies for environmental assessment in watersheds, mostly extend to large watersheds, comprising several municipalities, which hinders participatory management and effective. In general, proposed management alternatives for small watersheds guarantee the applicability of the methodology, as managements plans requiring the accession of several municipalities are not always applicable to lack of interest and participation of all municipalities involved. There is a need further studies and propose methodologies applicable to the definition of the intensity of environmental degradation in watersheds small, reaching a single municipality in order to subsidize the government to make decisions regarding the management, the recovery and the creation of areas of urban expansion, making the impacts of land use as small as possible. In this context, the objective of this research is to propose a cartographic model of environmental assessment of the physical environment for small watersheds of different land uses based on the concept of ecodynamics Tricart (1977). It was adopted as the study area Ilha Solteira - SP, which in 1968 had its urban layout planned and built to house workers in the construction of the hydroelectric plant of Ilha Solteira. The council was created on December 30, 1991. In this study, we will apply two different methodologies for assessing environmental quality, the environmental fragility of Crepani et al (1996) and diagnostic physical conservationist watershed adapted Beltrame (1994). As a result, the research developed a cartographic model entitled Diagnosis of the Physical, which in comparison with the other models tested, had defined borders between classes making the map cleaner and simplified. It is noteworthy that all these map products will provide subsidies for public decision-making in order to minimize future...

As bacias hidrográficas de pequeno porte influenciam diretamente na qualidade de vida dos municípios, e as metodologias de diagnóstico ambiental em bacias hidrográficas, em sua maioria, se estendem a bacias hidrográficas de grande porte, que compreendem vários municípios, o que dificulta uma gestão participativa e eficaz. Em geral, propor alternativas de gestão para pequenas bacias hidrográficas garantem a aplicabilidade da metodologia, visto que planos de manejos que necessitem da adesão de vários municípios nem sempre são aplicáveis pela falta de interesse e participação de todos os municípios envolvidos. Fazem-se necessários estudos mais detalhados e a proposição de metodologias aplicáveis para a definição da intensidade da degradação ambiental em bacias hidrográficas de pequeno porte, que atinjam um único município, a fim de subsidiar o poder público para a tomada de decisões referentes ao manejo, a recuperação e a criação de áreas de expansão urbana, tornando os impactos do uso da terra os menores possíveis. Neste contexto, o objetivo desta pesquisa foi propor um modelo cartográfico de diagnóstico ambiental do meio físico para bacias hidrográficas de pequeno porte, com usos da terra diferenciados, baseado no conceito de ecodinâmica de Tricart (1977). Adotou-se como área de estudo Ilha Solteira - SP, que em 1968 teve o seu traçado urbano planejado e construído para abrigar os trabalhadores na construção da Usina Hidrelétrica de Ilha Solteira. Nesse estudo, foram aplicadas duas metodologias distintas de avaliação de qualidade ambiental: a de “fragilidade ambiental” de Crepani et al (1996) e a de “diagnósticos físico-conservacionista de bacias hidrográficas” adaptado de Beltrame (1994). Como resultado, a pesquisa desenvolveu um modelo cartográfico intitulado Diagnóstico do Meio Físico, que em comparação com os outros modelos testados, apresentou limites entre as classes mais...
Keywords: Physical geography - Environmental aspects; Geografia física - Aspectos ambientais; Bacias hidrograficas; Qualidade ambiental; Geotecnologia ambiental; Diagnostico; Ilha Solteira (SP)